PENERAPAN E-LEARNING DALAM INOVASI PENDIDIKAN UNTUK MENINGKATKAN KEMAMPUAN LITERASI DIGITAL SISWA - Arfadila, Arfadila; Aulia, Erlinda Risa Nur; Nugraha, Reska Widyaksana; Humaeroh, Siti (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Our research aims to be able to analyze e-learning learning systems in an effort to improve digital literacy skills for students in the 21st century. Given that technology has penetrated into many human activities, including teaching and learning activities, it needs to be used optimally so that learning is not only a process of knowledge transfer but also as an increase in literacy skills for students. This research uses literature study method. Where will be obtained a conclusion from the findings of previous research that is focused on certain data sources. The results show that the application of e-learning is related to digital literacy. E-learning can make students become independent in finding information which can also train students' critical thinking patterns towards information that is obtained or received. The background for choosing this research is because we see from the phenomena that occur around us that today's technology is sometimes not optimized, therefore it is necessary to integrate basic things such as from the world of education. Where with education there will be a learning process and training skills which are certainly useful in the 21st century. The conclusion from our research is that the application of e-learning has a good impact on increasing students' digital literacy. Moreover, currently the application of e-learning has not been fully implemented in Indonesia, so this has become an innovation that needs to be promoted in all schools in every educational unit. Because as students adapt to the 21st century, we are required to have good literacy such as digital literacy as a way of receiving information.